A história da República passa por aqui! Camocim-CE (1889-1950) - Santos, Carlos Augusto Pereira dos (2019)
The municipality of Camocim was created by Law No. 1849, of September 29, 1879, year 58 of Independence and the Empire. The Villa de Camocim, therefore created by this act, signed by the then President of the Province, José Júlio de Albuquerque Barros, future Baron de Sobral, the same who, two years earlier, had beaten the first nail for the construction of the Railroad of Sobral in Camocim, remained with the same limits as when it was district of the municipality of Granja. Ten years later, still in the Empire and three months before the advent of the Republic, the then village received city forums by Law No. 2,162 of August 17, 1899. So, if we wished, we could celebrate two dates - September 29 and the 17 of August.